Operational Capacity on Policy Capacity in the Development of Regional Potential of South Bolaang Mongondow Regency - Kamaru, Iskandar (KnE Social Sciences, 2025)
The development of superior potential requires quality policy capacity so that it can optimize the output and impact of policies on regional development. This research aims to explore operational capacity on policy capacity in the development of superior potential in the South Bolaang Mongondow Regency. This research uses a qualitative study with a case study strategy, with an exploratory type. The research informants consisted of leaders of regional apparatus organizations (OPD) who have a domain of duties and responsibilities to optimize the development of regional superior potential. Data sources consist of primary and secondary data. The types of data collection consisted of focus group discussions, observations, in-depth interviews, and documentation studies. Data analysis consists of the stages of data collection, data reduction, and conclusion drawing. The findings demonstrated that South Bolaang Mongondow Regency’s agricultural, fisheries, tourism, and cattle industries have the greatest regional potential. Regional policies guide the creation of policies, which are then centrally coordinated and planned by the Regional Development Planning, Research, and Development Agency. Technical OPDs, such as the Agriculture Office, Fisheries Office, and Tourism Office, then implement programs and activities, followed by sub-districts and communities. At the operational stage, there are various obstacles such as human resources, infrastructure, and budget in developing superior potential in various sectors. Therefore, it is hoped that the local government will be able to comprehensively increase policy capacity so that the development of regional superior potential can be carried out optimally.